Symbolic computation of the time‐dependent electric and magnetic fields in bi‐anisotropic media with polynomial inputs. (30th March 2018) - Yakhno, Valery; Altunkaynak, Meltem
Abstract: A new method for the computation of a solution of the Maxwell's equations in bi‐anisotropic media with polynomial input is suggested. This method consists of the reduction of Maxwell's equations to a symmetric hyperbolic system of the first‐order partial differential equations. The solutions of the obtained system are constructed by symbolic computation in Maple for the given polynomial data in an explicit form. For the case when input data are given as smooth functions, an interpolation of the data has been made by polynomials and then an approximate solution has been computed by our method. The robustness of the method is confirmed by computational experiments. The comparison of the suggested method with finite difference time domain method has been done.